PERIODONTITIS DAN DIABETES MELITUS - Ermawati, Tantin (Fakultas Kedokteran Gigi Universitas Jember, 2012)
Periodontitis is a chronic infection disease caused by periodontopathogen bacteria in the oral cavity. Severity of periodontitis can be affected by systemic diseases such as diabetes mellitus. Diabetes mellitus is occurred metabolic disruption that is characterized by hyperglycemia due to insulin deficiency. Increasing blood glucose levels can lead to manifestations in the oral cavity in the form of inflammation of the gingival tissue, attachment loss and alveolar bone destruction. Periodontitis is one of the sixth complications of diabetes mellitus. There are inter- related relationship between periodontitis and diabetes mellitus.